Composition optimization of polyvinyl alcohol/rice starch/silk fibroin-blended films for improving its eco-friendly packaging properties - Kuchaiyaphum P. (2014)
Biopolymers obtained from renewable sources have been exploited in developing biomaterials with eco-friendly properties. Most biopolymers have some limitations because of their poor mechanical properties, high water solubility, or low transparencies. In this study, some biopolymers, that is, silk fibroin (SF) and rice starch (RS) were used as starting materials together with polyvinyl alcohol (PVA) as a film-former for preparing novel eco-friendly films. The film preparations were done by solution casting with two different sequences of blending and the film compositions were optimized. Results from UV, SEM, and film properties testing on mechanical properties, degree of swelling, water solubility, and also oxygen permeability indicated that all film properties depended on their compositions and order of blending. The PVA/RS film obtained is transparent with good mechanical properties and low water solubility. The addition of SF increases the permeability of oxygen and also the degradability of the films. Copyright © 2013 Wiley Periodicals, Inc.